To rearrange the equation \( G = H - TS \) for the quantity \( T \), we first isolate the term \( TS \):
\[ G = H - TS \]
Rearranging gives:
\[ TS = H - G \]
Now, to solve for \( T \), we divide both sides by \( S \):
\[ T = \frac{H - G}{S} \]
Now, none of the provided options appear to have the exact same form. We can observe that \( H - G \) can also be represented as \( -(G - H) \). However, we are looking for an expression with \( T \).
If we rewrite the previous expression in the context of the options provided:
In terms of the options given, we don't have \( G \) or \( H \) presented directly, however, we can check if any of the options directly match the form derived above.
- \( T = \frac{6}{s} + H \)
- \( T = \frac{G - \mu}{s} \)
- \( T = \frac{6}{s} - H \)
- \( T = \frac{-6 + 8}{s} \)
To analyze which of these might be close, we see:
- None of these seem to resemble \( T = \frac{H - G}{S} \).
- The first option doesn’t relate, the second involves \( \mu \) which is an unknown symbol, the third involves both positive and negative shifts on \( H \) that would mismatch with a rearrangement of our original equation in terms of \( G \), and the last has arbitrary constants.
Given there is no further context to equate \( \mu \) or to assess potential values for \( H \), there doesn’t seem to be enough information to conclude equivalently.
So, from our derived formula, the treatment can be simplified as:
\[ T = \frac{H - G}{S} \]
Now, it actually appears none of the provided options are correct based on our rearrangement.
Conclusively, if we take \( S = s \) in our considerations and eventually consider some linear combinations or values we might have missed, we'd even deduce that:
- If \( 6 = H \) and \( G = 8 \), thus symbolic for ratio of \( H \) and some equations, but ill-matched nonetheless.
Hence, upon evaluation, strictly none from the options provided correctly reflect a correct transformation based on the derived rearrangement of \( G = H - TS \).